Analisis Mekanisme Penetapan Harga Jual dalam Perspektif Prinsip Ekonomi Syariah: Studi Kasus pada Pasar Modern di Kabupaten Bone - Syakir, Aliyah Sri Huriyah; Haerul Nisa; Masyhuri (Journal of Islamic Economic Studies, 2025)
This research aims to analyze the suitability of the pricing mechanism applied by business actors in the modern market of Bone Regency with the principles of Islamic economics. The methodology used is a qualitative approach with a case study method. Data is collected through observation, in-depth interviews, and documentation from business actors and consumers. The results of the study indicate that most business actors have not fully applied the principles of Islamic economics in pricing. The use of an odd pricing system that does not align with the applicable currency denomination creates elements of uncertainty (gharar) and potential loss (dharar) for consumers. These findings emphasize the importance of applying principles of fairness, honesty, and transparency in pricing to create ethical transactions and enhance consumer trust in business actors.